Pengaruh Pengetahuan Perpajakan, Pemahaman Program Pelayanan Samsat, Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor (Studi Kasus Pada Kantor SAMSAT Denpasar) - Ni Made Putri Udiyani (Universitas Sains dan Teknologi Komputer, 2022)
Taxpayer compliance is the condition of a person carrying out his responsibilities as a citizen in an obedient manner that is in line with the laws of the Republic of Indonesia. Motor Vehicle Taxpayer Compliance is a tax responsibility carried out by Taxpayers who have ownership of their motorized vehicles. This study aims to determine the effect of tax knowledge, understanding of the SAMSAT service program, and awareness of taxpayers on motor vehicle tax compliance at the Denpasar SAMSAT Office. This research was conducted at the Denpasar SAMSAT Office. The method of determining the sample in this research is non-probability sampling with a purposive sampling method. The data analysis technique in this study is multiple linear regression. The results showed that knowledge of taxation, understanding of the SAMSAT service program, awareness of taxpayers had a positive effect on taxpayer compliance with motorized vehicles which indicated that the higher knowledge of taxation, understanding of the use of the SAMSAT program, and awareness possessed by taxpayers, this indicated high compliance. owned by the taxpayer. The implication of this research is to prove the application of the theory of panned behavior and technology acceptance model, as well as provide benefits for parties who have interests related to increasing motor vehicle tax compliance.